¿Una “biopolítica democrática”? Formas de resistencia al poder a través de su resignificación - Smith Pacheco, Vera (2023)
In this article, I explore the concept of democratic biopolitics in order to evaluate its viability. At the same time, I propose the context of this concept as a theoretical tool to analyze social injustice. Considering this perspective, the idea of power as having a priori a negative sign or, in other words, the idea that power itself implies merely an aggressive practice and domination is questioned. In addition, I address concepts such as the relational component of power, solidarity as a resistance practice and the questioning of the subject as theoretical elements of power with the purpose of contributing to a critique of different and violent scenarios where power explodes and subjugates.